Handbook of Pediatric Surgery - Sinha, Chandrasen K.; Davenport, Mark.; SpringerLink (Online service) (London : Springer London, 2010)
Handbook of Pediatric Surgery is an extensive yet concise distillation of the knowledge in its field, making for an ideal day-to-day reference guidebook. The sections include: Principles of Surgical Science; Fetal and Neonatal Surgery; General Children$1 (Bs Surgery; Principles of Pediatric Urology; Surgery of the Liver, Pancreas and Bile Ducts; Principles of Surgical Oncology; Pediatric Surgery in Clinical Practice; and Spina Bifida & Hydrocephalus. Written by distinguished authors from across the world, this book presents an international coalescence of perspectives that the reader will find truly enriching and instructive. Chandrasen K. Sinha is a Specialist Registrar in Pediatric Surgery at King$1 (Bs College Hospital in London, UK. Mark Davenport is a Consultant Pediatric Surgeon at King$1 (Bs College Hospital in London, UK.s
Milestones in Pediatric Surgery -- Milestones in Pediatric Surgery -- Principles of Surgical Science -- Fluids, Electrolytes, and Dehydration -- Metabolic Response to Injury and Sepsis -- Shock -- Parenteral Nutrition -- Hematology for Surgeons -- Postoperative Problems -- Neonatal Physiology and Care -- Fetal and Neonatal Surgery -- Fetal Surgery: General Principles -- Diaphragmatic Hernia -- Esophageal Atresia -- Pyloric Stenosis -- Malrotation -- Intestinal Atresia -- Necrotizing Entercolitis -- Meconium Ileus -- Hirschsprung$1 (Bs Disease -- Anorectal Malformations -- Abdominal Wall Defects -- Children$1 (Bs Surgery -- Surgical Neck Pathology -- Developmental Lung Anomalies -- Gastro-Esophageal Reflux -- Gastrointestinal Bleeding -- Acute Abdomen -- Intussusception -- Appendicitis -- Rare Causes of Abdominal Pain -- Crohn$1 (Bs Disease -- Ulcerative Colitis -- Short Bowel Syndrome -- Intestinal Transplantation -- Vascular Malformations -- Inguinal Hernias and Hydroceles -- The Acute Scrotum -- The Undescended Testes -- Miscellaneous Problems of the Male Genitalia -- Miscellaneous Surgical Issues -- Basic Pediatric Laparoscopy and Thoracoscopy -- Principles of Pediatric Urology -- Urinary Tract Infection -- The Ureter -- Vesico-Ureteric Reflux -- Neurogenic Bladder -- Posterior Urethral Valves -- Hypospadias -- Bladder Exstrophy, Epispadias, and Cloacal Exstrophy -- Disorders of Sex Development -- Surgery of the Liver, Pancreas and Bile Ducts -- Investigation of Jaundice -- Biliary Atresia -- Choledochal Malformations -- Gallbladder Disease -- Portal Hypertension -- Pancreatic Disease -- Liver Transplantation -- Principles of Surgical Oncology -- Wilms$1 (BTumor -- Liver Tumors -- Neuroblastoma -- Teratomas -- Miscellaneous Tumors -- Principles of Trauma -- General Principles -- Abdominal Trauma -- Thoracic Trauma -- Basic Brain Injury -- Spina Bifida and Hydrocephalus -- Spina Bifida -- Hydrocephalus -- Appendices -- Reference Weights and Heights -- Anatomical Reference -- Human Developmental Milestones.s
Keywords: Medicine; Pediatrics; Surgery; Medicine & Public Health; Pediatric Surgery; General Surgery; Pediatrics